Significant improvements in the mechanical properties of chitosan functionalized carbon nanotubes/epoxy composites. Issue 31 (10th March 2016) - Zhang, Yue; Huang, Shasha
Abstract : TEM image of the fracture structure of CNTs/CS/EP. Abstract : The CNTs–CS/EP nanocomposites with high mechanical properties were prepared by incorporating chitosan-grafted carbon nanotubes (CNTs–CS) in the epoxy resin. The CNTs–CS was synthesized by grafting chitosan onto the carboxylated CNTs in acetic acid aqueous solution. The chitosan played an important role as connectors between the CNTs and epoxy matrix. TGA and TEM results showed that the content of the chitosan grafts on the CNTs was about 22 wt%, and the thickness of the CS shell is about 10 nm. As compared with the un-grafted CNTs, the CNTs–CS exhibited a significantly improved dispersion in the epoxy matrix, resulting in dramatically improved mechanical properties. Compared with the pure epoxy, the impact strength and tensile strength of the nanocomposites with 1.5 wt% of CNTs–CS filler were enhanced surprisingly by about 87% and 79%, respectively. Hence, the CNT–CS assembly will open the way to the preparation of nanocomposites and the chitosan has promising applications in the aspect of preparing environment-friendly composites.